Estimation of residual stress distribution in railway axles. (May 2022) - Dlhý, Pavol; Poduška, Jan; Pokorný, Pavel; Jambor, Michal; Náhlík, Luboš; Kajánek, Daniel; Fajkoš, Rostislav; Hutař, Pavel
Highlights: General methodology to determine the residual stress distribution in railway axles is presented. The methodology was validated by measurements using neutron diffraction, X-ray diffraction and by slitting method. The applicability of the presented methodology is not limited to railway axles only. Abstract: The manufacturing process of railway axles usually includes axle surface treatment to induce compressive residual stress on the axle surface to increase impact resistance and fatigue lifetime. A proper determination of residual stress enables to obtain correct input data for other procedures, e.g., optimization of specialized treatment or lifetime estimation, which sets safe, but not unnecessary frequent, maintenance intervals of the axles. The most common methods for residual stress determination used by R&D centers of axle manufacturers are the hole drilling method and X-ray diffraction. However, we can use these methods for the determination of surface or close-to-surface residual stress only. In the case of large components like railway axles, it is essential to have information about the residual stress in the whole cross-section, not only from the axle surface, especially if the residual stress is developed by induction hardening, which can influence the residual stress distribution in a considerable depth. The work presented in this paper aims to develop a reliable methodology for determining residual stress in the whole cross-section of a railway axle with reasonable equipment prices or commonly used equipment. Two presented methods follow the defined methodology. They combine well-known destructive methods (layer removal and sectioning methods) with X-ray diffraction and numerical simulations to evaluate correct residual stress distribution. Both ways are applied to the case of an induction-hardened railway axle from the EA4T steel. Results of both methods are then compared to results obtained by neutron diffraction technique and other experimental methods to validate the plausibility of the proposed scenarios.